The Effects of Bio-inspired Electromagnetic Fields on Healthy Enhancement with Case Studies - Shujun Zhang; Mike Clark; Xuelei Liu; Donghui Chen; Paula Thomas; Luquan Ren (Ital Publication, 2019)
In this paper, an innovative bionic system will be presented. This system can be used to generate bio-inspired electromagnetic fields (BIEFM) by mimicking natural Earth magnetic fields, the frequencies, strengths and waveforms of body organs and cellular pulsations. The preliminary tests have been carried out to investigate the influences of BIEFM on the ATP levels of people to prove the interactions between BIEMF and the cellular level's bio-processing activities. This system has been applied for the health enhancement of humans and pets etc. A number of case studies will be present to demonstrate the efficiency and effectiveness of the system. The case study experimental results have shown that this innovative bio-inspired system works efficiently and effectively in enhancing human and animal health. It has been proven that this bio-inspired system can be effectively applied to many areas such as (1) human health enhancement and illness treatment, (2) pet health enhancement, and (3) reduction or elimination of 'jet lag'.